Green Synthesis of Silver Nanoparticles Using Sclerorhachis Leptoclada Rech. F. Leaf Extract: Characterization and Investigation of Antibacterial Activities - Ebrahim Shafaie; Zahra Salehi; Samira Eghbali (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: The environmentally friendly method of green nanoparticle production has garnered significant interest because of its cost-effectiveness and ease of implementation. In this study, in addition to the green synthesis of silver nanoparticles using the leaf extract of the Sclerorhachis leptoclada Rech. f. (SLL@AgNPs) and the morphological study of the SLL@AgNPs, the antibacterial properties of the SLL@AgNPs were compared with the extract of the S. leptoclada plant and silver nanoparticles alone. Methods: In this experimental investigation, the features of SLL@AgNPs synthesized via a green method were analyzed using various techniques, including spectrophotometry, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), dynamic light scattering (DLS), and transmission electron microscopy (TEM). Ultimately, the antibacterial properties were assessed through the broth micro-dilution method. Results: DLS and zeta potential showed the formation of SLL@AgNPs with a hydrodynamic diameter of 130 nm and a surface charge of -38.82 mV, respectively. XRD and TEM analysis also confirmed the formation of pure silver nanoparticles with spherical and elliptical morphology with an average diameter of 20-30. The SLL@AgNPs exhibited antibacterial activity against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis, with minimum inhibitory concentrations (MIC) of 0.039, 0.078, 0.039, 0.078, and 0.31 mg/ml, respectively. These findings indicate that SLL@AgNPs significantly enhanced the antibacterial properties of the S. leptoclada plant. Conclusion: As evidenced by the obtained results, S. leptoclada plant extract significantly increased the antibacterial activity of silver nanoparticles. This research demonstrated the potential of environmentally friendly silver nanoparticles synthesized in the presence of S. leptoclada extract with significant antibacterial effects for various biomedical applications.